PEMBERDAYAAN LAHAN TERBATAS MENGGUNAKAN TEKNOLOGI TEPAT GUNA PADA MASYARAKAT KELURAHAN SIDODADI SURABAYA - Eni Nurhayati; Ery Rahmawati; Anggra Lita Sandra Dewi; Galuh Kartika Dewi; Muhammad Faris Abdil Aziz (STKIP PGRI Sidoarjo, 2023)
The city of Surabaya is the center of the city in East Java and is a densely populated city. City buildings, housing, shops, high-rise buildings in villages become densely packed, giving rise to air pollution problems. With the problem of air pollution, it is necessary to carry out reforestation in Surabaya, one of which is in the Sidodadi area, Sidotopo District, Surabaya. In the Sidodadi area, there is still limited vacant land but it has not been utilized properly by local residents. Seeing the potential and existing problems, lecturers at STKIP PGRI Sidoarjo and UPN Veteran Surabaya carried out community service by empowering limited land using appropriate technology in the Sidodadi sub-district community, Surabaya. The target of this activity is the community around the sub-district. The method used in this service begins with counseling about the importance of greening in urban areas and socialization of hydroponic techniques and the benefits of family medicinal plants (TOGA), then continues with independent practice of planting TOGA using hydroponic techniques on limited empty land. The result of this service activity is that the community is enthusiastic in participating in activities both during counseling and independent practice. With this activity, the people of Sidodadi Surabaya gained knowledge about hydroponic technology and were able to utilize limited land so that the Sidodadi Surabaya area became greener.